Literature Review on the Potential of Pleurotus spp. Fungal Mycelium as a Biodegradable Packaging Material for Styrofoam Replacement - Adhania Andika Prayudanti; Dwirini Kartikasari; Indra Wirawan (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2026)
This literature review aimed to: (1) identify edible fungal species with potential applications as mycelium-based packaging materials; (2) compare mycelial characteristics in terms of substrate compatibility, mechanical properties, thermal stability, water absorption, and food safety; and (3) recommend the most suitable species for the development of biodegradable food packaging. A systematic scoping review was conducted following the framework of Arksey & O’Malley (2005) and PRISMA-ScR guidelines. Literature searches were performed in Scopus, Web of Science, ScienceDirect, and Google Scholar for publications from 2015 to 2024 using the keywords mycelium composite, mycelium-based foam, Pleurotus packaging, and biodegradable packaging fungi. Of the 312 articles initially identified, 47 met the inclusion criteria, namely empirical studies that assessed at least two material parameters and were published in English or Indonesian. The findings indicate that Pleurotus ostreatus exhibits several advantages, including rapid colonization time (7–14 days), suitable mycelium density (25–75 kg/m³), tensile strength (0.18–0.43 MPa), low thermal conductivity (0.03–0.07 W/m·K), and a high biodegradation rate in soil (60–90% per week). Pleurotus citrinipileatus demonstrated slightly lower mechanical performance but greater adaptability to mixed substrates. Both species are classified as generally recognized as safe (GRAS) by the FDA and do not produce significant levels of mycotoxins under standard cultivation conditions. Overall, P. ostreatus shows strong potential as a biodegradable packaging material to replace expanded polystyrene (EPS). However, industrial-scale experimental validation, food contact migration testing, and production standardization remain essential before commercial application.